2021
DOI: 10.1159/000512848
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of ACEI/ARB on Left Ventricular Function in Anthracycline-Induced Chronic Cardiotoxicity: A Meta-Analysis of Randomized Controlled Trials

Abstract: <b><i>Purpose:</i></b> Cardiotoxicity is an important side effect of anthracycline. Cardioprotective drugs for anthracycline remain inconclusive. We attempted to determine the role of angiotensin-converting enzyme inhibitors (ACEI) and angiotensin-receptor blockers (ARB) in the prevention of anthracycline-induced cardiotoxicity. <b><i>Hypothesis:</i></b> Prophylactic use of ACEI/ARB reduces the clinical or subclinical cardiotoxicity of anthracycline. <b><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(43 reference statements)
0
8
0
1
Order By: Relevance
“…Based on current clinical guidance, patients presenting as pre-hypertensive would not be currently eligible for antihypertensive drug therapy [ 7 , 8 ]. Clinical trials are however underway to assess the potential use of antihypertensive angiotensin-converting enzyme inhibitors (ACEi) or angiotensin-receptor blockers (ARB) in the prevention of anthracycline-associated heart failure [ 14 ]. In several of these trials, whereas patients receiving antihypertensive medications are excluded, patients exhibiting pre-hypertension are included based on the fact their BPs are within the ‘normal’ range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on current clinical guidance, patients presenting as pre-hypertensive would not be currently eligible for antihypertensive drug therapy [ 7 , 8 ]. Clinical trials are however underway to assess the potential use of antihypertensive angiotensin-converting enzyme inhibitors (ACEi) or angiotensin-receptor blockers (ARB) in the prevention of anthracycline-associated heart failure [ 14 ]. In several of these trials, whereas patients receiving antihypertensive medications are excluded, patients exhibiting pre-hypertension are included based on the fact their BPs are within the ‘normal’ range.…”
Section: Discussionmentioning
confidence: 99%
“…In several of these trials, whereas patients receiving antihypertensive medications are excluded, patients exhibiting pre-hypertension are included based on the fact their BPs are within the ‘normal’ range. Preliminary results to date are encouraging with ACEi/ARB demonstrating a protective effect and reducing the cardiotoxic effects of anthracyclines [ 14 ]. However, due to the early stages of these studies and subsequent limited data available, it is not yet ascertained whether ACEi/ARB can mitigate anthracycline-associated heart failure or indeed the contribution played by pre-hypertension in development of these adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 The protective mechanism of ACEI includes the inhibition of ventricular remodelling. 57 Gupta et al assessed the role of enalapril in a randomised, double-blind, clinical trial in which measurements of LVEF (2-D echocardiography) and cardiac biochemical markers (cTnI, proBNP and CK-MB) were performed. After 6 months of treatment, significant differences were detected in the LVEF and mean levels of cTnI and proBNP.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Eliminating risk factors for CVD and moderate aerobic exercise may contribute to this effort [17, 36]. The use of β-blockers, angiotensin-converting enzyme inhibitors, or angiotensin receptor blockers to prevent cardiotoxicity still is controversial and is based on limited studies [36, 42]. More recently, it has been suggested that statins may decrease cardiotoxicity related to chemotherapy in patients with breast cancer [43].…”
Section: Effects Of Cancers On Cardiovascular Diseasementioning
confidence: 99%